2021
DOI: 10.1111/lam.13532
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm prevalence and microbial characterisation in chronic wounds in a Sri Lankan cohort

Abstract: Biofilms have been associated with chronic wound infections in diabetic patients. The study assessed the occurrence of biofilms in chronic diabetic wounds (CDWs) in a Sri Lankan cohort. Tissue specimens collected during surgical debridement were analysed by quantitative differential viable counting, scanning electron microscopy (SEM), fluorescence insitu hybridization (FISH) and light microscopy with Gram and Haematoxylin‐Eosin staining. All specimens harboured >5·0 log10 CFU per g bacteria and 2–9 distinct sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Cutaneous leishmaniasis lesions are chronic in nature. It has been reported that the prevalence of biofilms in non-cutaneous leishmaniasis chronic wounds is more than 78.2% 11,12 . We detected biofilms in 61.5% (24/39) of the cutaneous leishmaniasis lesions using fluorescence in situ hybridization in formalin-fixed paraffin-embedded tissue (FFPE-FISH).…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous leishmaniasis lesions are chronic in nature. It has been reported that the prevalence of biofilms in non-cutaneous leishmaniasis chronic wounds is more than 78.2% 11,12 . We detected biofilms in 61.5% (24/39) of the cutaneous leishmaniasis lesions using fluorescence in situ hybridization in formalin-fixed paraffin-embedded tissue (FFPE-FISH).…”
Section: Discussionmentioning
confidence: 99%
“…A Sri Lankan study on biofilms in diabetic wounds reported that most chronic diabetic foot wounds are colonized with Pseudomonas spp. [9]. Under similar settings, we found that the biofilms of ulcerated local CL wounds were mainly composed by class bacilli, family Enterobacteriaceae, and genus Pseudomonas [6].…”
Section: Main Textmentioning
confidence: 58%
“…The size of the CL wound biofilms (7-140 µm) [6] was lower than what has been reported with diabetic foot wounds (12-400 µm) [9]. This could probably be due to early sampling of the reported CL wounds [6] or the patchy distribution of biofilms.…”
Section: Main Textmentioning
confidence: 69%
See 1 more Smart Citation